Diarylamino-substituted tetraarylethene (TAE) as an efficient and robust hole transport material for 11% methyl ammonium lead iodide perovskite solar cells1. Issue 73 (21st September 2015) - Cabau, Lydia; Garcia-Benito, Ines; Molina-Ontoria, Agustin; Montcada, Nuria F.; Martin, Nazario; Vidal-Ferran, Anton; Palomares, Emilio
<x xml:space="preserve">Abstract</x> We report the synthesis and characterisation of tetra{4-[N, N-(4, 4′-dimethoxydiphenylamino)]phenyl}ethene (TAE-1) as an efficient and robust hole transport material for its application in methyl ammonium lead iodide (MAPI) perovskite solar cells.